Inclusive innovation for the promotion of regional food heritage: A case study of a small producers' fair model in urban spaces - Bernardo Alayza; Domingo González; Emilio Diaz; Hernán Cornejo; Maritza Canales (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología)
The current research develops a case study of a model of a Fair of small producers in urban spaces, discussing the implications of inclusive innovation processes from a regional food heritage perspective. Through gathering primary information, interviews and discussions with the protagonists and stakeholders, this study reveals innovation processes that have facilitated inclusive development taking into account the participation of rural small producers. The configuration of inclusive innovation processes has been evidenced by the assets, actors and the food community that have been created in the frame of the Fair. This has generated a new value to this initiative and has laid the basis for the consolidation of the Fair as a model that can be replied. The analysis allows us to affirm that the Fair constitutes a space for inclusive innovation due to it has built new networks with heterogeneous actors, it has capitalized various types of traditional knowledge and it has generated opportunities for small producers. From a cultural perspective, the regional food heritage that has been promoted by small producers in the Fair, has contributed to generating new capacities and opportunities in this population.